Best of both worlds - LIBER Quarterly (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
By the nineties of the twentieth century microfilming had finally reached a level of quality and durability that made it a safe and secure surrogate for books and documents that were threatened by acid paper decay. Large-scale microfilming programs were set up un the US (Library of Congress), Germany (DFG), France (BNF), England (Newsplan) and The Netherlands (Metamorfoze)